Reasons Why Patients Remain Uninsured after Massachusetts’ Health Care Reform: A Survey of Patients at a Safety-Net Hospital - Nardin, Rachel (Springer-Verlag, 2011)
BACKGROUND: Following the 2006 Massachusetts health care reform, an estimated 316,492 residents remain uninsured. However, there have been no published studies that examine why Massachusetts residents remain uninsured four years into health reform. OBJECTIVE: To describe the characteristics of uninsured patients seeking acute medical care in Massachusetts after implementation of health care reform and reasons for lacking insurance. DESIGN AND PARTICIPANTS: We performed an in-person survey of a convenience sample of patients visiting the emergency department of the state’s second largest safety net hospital between July 25, 2009 and March 20, 2010. We interviewed 431 patients age 18–64, 189 of whom were uninsured. MAIN MEASURES: Demographic and clinical characteristics, employment and insurance history, reasons for lacking insurance and views of the state’s new “individual mandate”. KEY RESULTS: The uninsured were largely employed (65.9%), but only a quarter (25.1%) of the employed uninsured had access to employer-sponsored insurance. The majority qualified for subsidized insurance (85.7% earned ≤300% of the federal poverty level), yet many reported being unable to find affordable insurance (32.7%). Over a third (35.2%) were uninsured because they had lost insurance due predominantly to job loss or policy cancellation. For nearly half of the uninsured (48.6%), the individual mandate had motivated them to try to find insurance, but they were unable to find insurance they could afford. CONCLUSIONS: After full implementation of the Massachusetts health reform, those remaining without insurance are largely the working poor who do not have access to, or cannot afford, either employer sponsored insurance or state subsidized insurance.